PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, KARAKTER EKSEKUTIF DAN SIZE TERHADAP TAX AVOIDANCE (Study Empiris Pada Emiten Sektor Perdagangan yang Terdaftar di BEI Tahun 2014-2017) - Giawan Nur Fitria (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
The purpose of this reseach is to know the effect of institutional ownership, independent Board of Directors, executive characteristics and size of firm to tax avoidance. This research is using 8 companies listed in Trading Sector in Indonesia Stock Exchange 2014 – 2017. This research was using 32 data financial reports from Indonesia Stock Exchange with multiple regression and process with SPSS 23. The result on partially, institutional ownership, independent of Board of Director, executive characteristics are have no significant effect to tax avoidance. While size of firm has significant effect to tax avoidance.